Structural Inequality of Land Ownership in Indonesia: A Justice-Based Legal Perspective - Agung Iriantoro; Junimart Girsang; Suwarno Suwarno (Jurnal Hukum, 2026)
Structural inequality in land ownership remains a pressing issue in Indonesia, where control over vast land areas is concentrated among corporations and elites, while many communities continue to face limited access to agrarian resources. This condition contributes to poverty, social vulnerability, and recurring agrarian conflicts across regions. This research aims to analyze the phenomenon of structural inequality in land ownership through a justice-based perspective, examining its root causes and assessing the effectiveness of existing agrarian policies. Using a normative juridical method with statute and conceptual approaches, the study reviews legal frameworks, policy documents, and academic literature to provide a comprehensive evaluation. The findings indicate that overlapping regulations, weak recognition of customary rights, pro-investment legal reforms, and limited public participation have hindered equitable land governance. Agrarian Reform policies have also fallen short, particularly in achieving meaningful redistribution, strengthening community rights, and providing adequate conflict resolution mechanisms. The study concludes that reducing structural inequality requires strengthening justice-oriented legal norms, improving coherence among agrarian regulations, enhancing recognition of local and customary rights, and ensuring more inclusive participation in policy implementation.